P3_9 Scooby and Shaggy: Metabolic Miracles - Moore, C. D.Y.; Buttery, H. W.; Middleton, C. J.; Peck, R. H. (Physics Special Topics, 2016)
In the cartoon `What's New Scooby-Doo?' the characters Shaggy and Scooby are seen to eat large volumes of food without gaining any weight. Their effective temperatures in order to radiate away the excess energy were calculated to be T_Sh 97 ± 033 °C for Shaggy, and T_Sc 140 ± 43 °C for Scooby. It was concluded that under normal circumstances, the subjects would perish of extreme hyperthermia. It was also noted that Shaggy could survive if he was able to sweat continuously at the maximum rate for a human.